(untitled) (Plant Tissue Culture and Biotechnology, 2018)
To evaluate the genetic diversity among 10 cultivars of anthurium were performed using three molecular markers such as Start Codon Targeted (SCoT) and Conserved DNA-derived Polymorphism (CDDP), and Random Amplification of Polymorphic DNA (RAPD). Polymorphism index content (PIC) was calculated 0.39, 0.42 and 0.37 for RAPD, SCoT and CDDP, respectively. This result showed all the three molecular markers had almost an identical potential in estimating genetic diversity. Cluster analysis using SCoT, CDDP and RAPD divided the cultivars to three distinct clusters. The similarity matrix obtained through SCoT and CDDP was positively significantly correlated (r = 0.76, p < 0.01). This is the first report in which the efficiency of two targeted DNA region molecular markers (SCoT and CDDP) together with RAPD technique have been compared with each other in a set of anthurium cultivras. Results suggested that SCOT, CDDP and RAPD fingerprinting techniques are of sufficient ability to detect polymorphism in anthurium cultivars. Plant Tissue Cult. & Biotech. 28(2): 171-182, 2018 (December)